RNA‐sequencing reveals oligodendrocyte and neuronal transcripts in microglia relevant to central nervous system disease. Issue 4 (24th September 2014) - Solga, Anne C.; Pong, Winnie W.; Walker, Jason; Wylie, Todd; Magrini, Vincent; Apicelli, Anthony J.; Griffith, Malachi; Griffith, Obi L.; Kohsaka, Shinichi; Wu, Gregory F.; Brody, David L.; Mardis, Elaine R.; et al.
<x xml:space="preserve">Abstract</x> Expression profiling of distinct central nervous system (CNS) cell populations has been employed to facilitate disease classification and to provide insights into the molecular basis of brain pathology. One important cell type implicated in a wide variety of CNS disease states is the resident brain macrophage (microglia). In these studies, microglia are often isolated from dissociated brain tissue by flow sorting procedures [fluorescence‐activated cell sorting (FACS)] or from postnatal glial cultures by mechanic isolation. Given the highly dynamic and state‐dependent functions of these cells, the use of FACS or short‐term culture methods may not accurately capture the biology of brain microglia. In the current study, we performed RNA‐sequencing using Cx3cr1+/GFP labeled microglia isolated from the brainstem of 6‐week‐old mice to compare the transcriptomes of FACS‐sorted versus laser capture microdissection (LCM). While both isolation techniques resulted in a large number of shared (common) transcripts, we identified transcripts unique to FACS‐isolated and LCM‐captured microglia. In particular, ∼50% of these LCM‐isolated microglial transcripts represented genes typically associated with neurons and glia. While these transcripts clearly localized to microglia using complementary methods, they were not translated into protein. Following the induction of murine experimental autoimmune encephalomyelitis, increased oligodendrocyte and neuronal transcripts were detected in microglia, while only the myelin basic protein oligodendrocyte transcript was increased in microglia after traumatic brain injury. Collectively, these findings have implications for the design and interpretation of microglia transcriptome‐based investigations. GLIA 2015;63:531–548